Adli Kontrol - Sırma Gezer, Özge; Saygılar Kırıt, Yasemin F. (Seçkin Yayıncılık, 2016)
5271 sayılı Ceza Muhakemesi Kanunu’nun yürürlüğe girmesi ile birlikte Türk ceza usul hukuku sisteminde yer edinen yeni koruma tedbirlerinden biri de adli kontrol tedbiridir. CMK’da yapılan değişikliklerle adli kontrol tutuklamaya alternatif bir koruma tedbiri olması öngörülmektedir.

Within the become effective of the Turkish Law of Criminal Procedure number 5271, we have some new protection measures in Turkish Criminal Procedures. In this article we will discuss one of these measures called Judical Control Measure.
Keywords: Ceza Muhakemesi Hukuku; Ceza Muhakemesi Kanunu; Adli Kontrol; Tutuklama; Koruma Tedbirleri; Criminal Procedure Law; Code of Criminal Procedure; Judicial Conrol; Arrest; Protection Measures